Morphological Indicators of a Mascon Beneath Ceres's Largest Crater, Kerwan. Issue 3 (12th February 2018) - Bland, M. T.; Ermakov, A. I.; Raymond, C. A.; Williams, D. A.; Bowling, T. J.; Preusker, F.; Park, R. S.; Marchi, S.; Castillo‐Rogez, J. C.; Fu, R. R.; Russell, C. T.
Abstract: Gravity data of Ceres returned by the National Aeronautics and Space Administration's Dawn spacecraft is consistent with a lower density crust of variable thickness overlying a higher density mantle. Crustal thickness variations can affect the long‐term, postimpact modification of impact craters on Ceres. Here we show that the unusual morphology of the 280 km diameter crater Kerwan may result from viscous relaxation in an outer layer that thins substantially beneath the crater floor. We propose that such a structure is consistent with either impact‐induced uplift of the high‐density mantle beneath the crater or from volatile loss during the impact event. In either case, the subsurface structure inferred from the crater morphology is superisostatic, and the mass excess would result in a positive Bouguer anomaly beneath the crater, consistent with the highest‐degree gravity data from Dawn. Ceres joins the Moon, Mars, and Mercury in having basin‐associated gravity anomalies, although their origin may differ substantially. Key Points: Ceres's largest crater Kerwan has unique morphology: the deep center rises concavely to a broad topographic bench interior to the rim The morphology can be produced by viscous relaxation of the crater in a crust which thins substantially beneath the crater floor The inferred high‐density material beneath Kerwan would produce a positive gravity anomaly, consistent with data from NASA's Dawn mission